Aplicación de protocolos de asepsia y antisepsia en el entorno quirúrgico: una revisión sistemática - Noroña Martínez, Clara Abigail (2026)
Surgical site infections constitute a serious public health problem, due to their high morbimortality rate, prolonged stays and high cost. This study aimed to evaluate the application of asepsis and antisepsis protocols in the prevention of infectious complications through a systematic review of scientific literature published between 2020 and 2025. From the total of 701 identified records, 35 studies were analyzed, chosen using the PRISM method, having as exclusion criteria narrative reviews, languages other than those specified, undergraduate theses, studies that do not meet quality criteria, recognizing that protocols combining alcoholic chlorhexidine (2-4%), antisepsis times ≥3 minutes, systematic review and continuous training reduce SSIs between 37-55%. The results showed that strict adherence to protocols reduces hospital contaminations, although their implementation requires adjustment to the local context and overcoming structural obstacles. The findings show that multimodal interventions that integrate technology, audits and continuing education are an effective strategy for the prevention of SSIs. These findings offer inputs to reinforce institutional clinical guidelines and to regularize safe surgical interventions, essentially in second and third level hospitals.